2016
DOI: 10.1007/s11356-016-7138-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and its associated factors in contaminated areas of the Santos-São Vicente Estuarine region and Bertioga, Brazil: 2006-2009

Abstract: In Brazil, cardiovascular diseases account for 33% of deaths and the prevalence of hypertension is of approximately 22%. The Santos and São Vicente Estuarine System is the most important example of environmental degradation by chemicals from industrial sources. The aim of the present study was to evaluate the prevalence of hypertension and its associated factors in the population of this estuary in the period 2006-2009. A cross-sectional study was conducted to assess the aforementioned prevalence of hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…The prevalence of AH was 74.9%, higher than observed in the country's adult population shown by other studies carried out in different regions. 8 , 11 , 12 , 19 - 21 The prevalence of AH in individuals aged between 50 and 70 years is approximately 6 to 8-fold higher than that in young adults, aged between 18 and 29 years, 19 - 22 consistent with 16 studies carried out in the country between 1989 and 2007, which reported prevalence rates of AH higher than 60% in the elderly population. 10…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The prevalence of AH was 74.9%, higher than observed in the country's adult population shown by other studies carried out in different regions. 8 , 11 , 12 , 19 - 21 The prevalence of AH in individuals aged between 50 and 70 years is approximately 6 to 8-fold higher than that in young adults, aged between 18 and 29 years, 19 - 22 consistent with 16 studies carried out in the country between 1989 and 2007, which reported prevalence rates of AH higher than 60% in the elderly population. 10…”
Section: Discussionsupporting
confidence: 75%
“…Canada has a rate of 64.6%, 31 Switzerland has 59.4%, 32 the United States has 57% 33 and England, 37%. 34 In Brazil, these rates vary between 22.5% in the North region 11 and 24.2% in the Midwest. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Publication dates of included articles spanned from 1980 to 2021; however, 22 out of 25 studies were published after 2000. Ten studies (40%) were conducted in the Global South, eight of these being in Nigeria [ 21 – 28 ], one in Brazil [ 29 ], and one in Ecuador [ 30 ]. The majority of the studies ( n = 15) were conducted in Urban settings in developed countries, including Taiwan, Italy, United States, and Spain.…”
Section: Resultsmentioning
confidence: 99%
“…Cerca de un billón de adultos en el mundo tiene esta enfermedad, encontrándose las mayores prevalencias en Europa del este, Latinoamérica y Caribe 3 . Diversos estudios realizados en Brasil han observado en adultos prevalencias de hipertensión que fluctúan entre el 22% y el 68% [4][5][6][7][8][9] .…”
Section: Introductionunclassified